2008
DOI: 10.1152/ajpendo.90359.2008
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin secretion and response to pioglitazone is depot dependent in cultured human adipose tissue

Abstract: To test the hypothesis that depot differences exist for adiponectin, fresh and cultured human VAT and SAT from obese type 2 diabetic (T2D) and obese nondiabetic (ND) subjects was examined to determine whether differences in adiponectin content and secretion occurred as a function of depot studied, diabetic status, and response to thiazolidinedione treatment. VAT and SAT were obtained by biopsy and AT explants cultured in defined media for 7 days. Protein expression was assessed by Western blot. Adiponectin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
46
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 64 publications
12
46
0
1
Order By: Relevance
“…Motoshima et al 11 and Perrini et al 3 reported that the cultured human omental adipocytes secrete more adiponectin than subcutaneous adipocytes and that its secretion is inversely correlated to BMI, whereas the secretion from the subcutaneous cells was unrelated to BMI. Contrary to this, Phillips et al 29 showed lower adiponectin levels secreted by VAT than SAT explants of obese as well as type 2 diabetic people. These inconsistent findings may be attributed to important methodological differences existing among the studies comparing AT explant cultures and adipocyte cultures.…”
Section: Discussionmentioning
confidence: 83%
“…Motoshima et al 11 and Perrini et al 3 reported that the cultured human omental adipocytes secrete more adiponectin than subcutaneous adipocytes and that its secretion is inversely correlated to BMI, whereas the secretion from the subcutaneous cells was unrelated to BMI. Contrary to this, Phillips et al 29 showed lower adiponectin levels secreted by VAT than SAT explants of obese as well as type 2 diabetic people. These inconsistent findings may be attributed to important methodological differences existing among the studies comparing AT explant cultures and adipocyte cultures.…”
Section: Discussionmentioning
confidence: 83%
“…In fact, different protein production or gene expression of many adipocytokines, including adiponectin, was demonstrated in visceral when compared with subcutaneous fat. The results are not unequivocal: lower adiponectin protein and mRNA levels in visceral versus subcutaneous AT were evidenced in several studies (46,47) while opposite results were reported by other authors (48,49). To date, no study on adiponectin isoforms secretion by visceral AT explants has been reported.…”
Section: Discussionmentioning
confidence: 84%
“…Nonetheless, the temporal resolution of the technique is of importance to detect a correct trend when changes from baseline levels are ad- dressed (25). Second, although the characterization of interstitial adiponectin in the sc abdominal AT may not reflect the activity of the whole-body fat, different data indicate that this depot exerts a greater influence on circulating adiponectin than the visceral fat (2,34,35,46). Third, the nonreducing SDS-PAGE may be technically challenging to quantify precisely the adiponectin oligomers also because the Alb-LMW is difficult to separate from the other forms (1,9).…”
Section: Discussionmentioning
confidence: 99%